Students' Perceptions of Stress, Intonation, and Rhythm in English Communication - Sifa Askya; Aslimah Nur; Cindy Arianti Damanik; Yani Lubis (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
Suprasegmental elements such as stress, intonation, and rhythm play a fundamental role in spoken English communication, yet they remain consistently underrepresented in English as a Foreign Language (EFL) teaching and curriculum design. This conceptual paper synthesizes current empirical research to examine how EFL learners perceive these three prosodic features and to explore the pedagogical implications of such perceptions for pronunciation instruction. Drawing on studies in applied linguistics, second language acquisition (SLA), and pronunciation pedagogy, this paper reveals that learners generally acknowledge the communicative significance of stress and intonation, while rhythm remains the least understood and most pedagogically neglected feature across different proficiency levels. A recurring finding across studies is the persistent gap between learners’ theoretical awareness of suprasegmental features and their practical confidence in producing these features during real-time, spontaneous communication. This gap is attributed to limited explicit instruction, the abstract nature of prosodic features, and the influence of learners’ native language rhythmic patterns. The paper further identifies that EFL learners tend to view intonation as the most communicatively important but also the most cognitively demanding suprasegmental feature, while stress receives moderate attention and rhythm is frequently misunderstood or overlooked entirely. Based on these findings, the article advocates for explicit, integrated, and communicatively embedded teaching of suprasegmental features in EFL classrooms. Practical instructional strategies—including shadowing, rhythm-tapping, and discourse-level intonation analysis—are discussed as means to bridge the divide between learners’ suprasegmental knowledge and their oral performance.